The relationship between gestational age and the severity of neonatal abstinence syndrome. (4th January 2017) - Gibson, Kelly S.; Stark, Sydney; Kumar, Deepak; Bailit, Jennifer L.
Abstract: Background and aims: The relationship between gestational age at delivery and the severity of neonatal abstinence syndrome (NAS) is poorly understood. Our objective was to compare the length of pharmacotherapy and hospital stay among opioid‐exposed infants born during the late pre‐term, early term, full term and late term periods. Design: Retrospective cohort study of infants affected by NAS. Setting: MetroHealth Medical Center in Cleveland, OH, USA: an urban tertiary care hospital serving as the referral center for opioid dependency in pregnancy with a level III neonatal intensive care unit. Participants: All deliveries complicated by maternal opioid exposure from January 2000 to October 2014; 403 were eligible to be included [ n  = 102 late pre‐term, 34–36 weeks (LP), n  = 158 early term, 37–38 weeks (ET), n  = 122 full term, 39–40 weeks (FT), n  = 21 late term, ≥41 weeks (LT)]. Measurements: NAS requiring pharmacotherapy with opioids and hospital stay duration were compared between gestational age cohorts. Interaction by type of maternal medication was evaluated. Findings: The necessity for pharmacotherapy for NAS was similar in all gestational age groups [LP  n  = 45/102 (44%), ET n  = 65/158 (41%), FT n  = 55/122 (45%), LT n  = 9/21 (43%); P  = 0.92]. However, the median duration of pharmacotherapy for NAS was significantly different between the groups [LP =16.0 median (interquartile range: IQR = 10.0–24.0) days, ET = 22.5 (IQR = 15.0–40.0), FT = 23.0 (IQR = 6.0–38.0), LT = 22.0 (IQR = 6.0–28.0); P  = 0.02]. Neonatal intensive care unit admission for NAS ( P  = 0.07) and total length of stay ( P  = 0.27), which includes observation for NAS not requiring medication, were not different. There was no significant interaction between gestational age cohorts and maternal medication assisted treatment therapy on the need for or duration of NAS treatment. The results were unchanged when evaluated for potential confounding variables. Conclusions: Gestational age (pre‐term, term or late term) at birth appears to be unrelated to the need for pharmacotherapy to treat neonatal abstinence syndrome (NAS) in late pre‐term and term infants. If treatment is needed it may tend to be given for longer in term than pre‐term or late term infants.